The Precarious Geopolitics of Urban Encounters in Jonathan Safran Foer's Extremely Loud and Incredibly Close (2005) - Shona Loong Xiu Fen (Taylor & Francis, 2018)
Geografiska Annaler: Series B, Human Geography